PENGUJIAN SIFAT MEKANIK PENGELASAN DISSIMILAR PADA BAJA AISI 1045 DAN AISI 4140 DENGAN METODE TUNGSTEN INERT GAS (TIG): PENGUJIAN SIFAT MEKANIK PENGELASAN DISSIMILAR PADA BAJA AISI 1045 DAN AISI 4140 DENGAN METODE TUNGSTEN INERT GAS (TIG) - Lestari, Nidia (Fakultas Teknik Universitas Wahid Hasyim, 2025)
Metal joining techniques have developed rapidly nowadays, one of which is metal joining with the Tungsten Inert Gas (TIG) welding technique. This welding technique allows joining between metals that have different material properties. One of them is welding between AISI 1045 and AISI 4140. In this study, dissimilar welding was carried out on AISI 1045 and AISI 4140 steel materials by varying the electric current in welding (A) namely 90A, 100A, and 110A. For the shape of the specimen used in this study is a solid cylinder with a diameter of 19 mm. Where, the filler used is ER309L rod as a filler material. The strength of the welding joint was tested by conducting tensile tests, bending tests, and impact tests. Then the data obtained were analyzed and discussed based on correlation statistics and hypothesis testing from statistical calculations between variations in electric current, it can be concluded that the higher the electric current, the lower the tensile strength and bending stress and the more brittle the results of the welded joint.